Optimizing physical fitness in chronic stroke patients: the impact of exercise training modality and dosage on maximal and sub-maximal fitness – a systematic review and meta-analysis - Felix Nindorera; Clement Leveque; Eric Meyer; Costantino Balestra; Sigrid Theunissen (Journal of Rehabilitation Medicine)
Objective: To evaluate the effects of different exercise training modalities on maximal and sub-maximal physical fitness in chronic stroke patients and determine the optimal training dosage.